"The Big Society, " Public Expenditure, and Volunteering. (20th December 2012) - Bartels, Koen P. R.; Cozzi, Guido; Mantovan, Noemi
<x xml:space="preserve">Abstract</x> The debate on volunteering has paid insufficient attention to the relationship between public spending and volunteering. The importance of this relationship is highlighted by the British government's "Big Society" plan, which asserts that an increase in volunteering will compensate for the withdrawal of public agencies and spending. This idea is based on the widely held belief that a high degree of government intervention decreases voluntary activities. This article uses a multidisciplinary approach to improve understanding of how public spending affects the decision to volunteer. A theoretical model conceptualizes this relationship in terms of time donation by employed individuals. The model is tested empirically through an econometric analysis of two survey data sets and interpretative analysis of narratives of local volunteers and public professionals. The results suggest that volunteering is likely to decline when government intervention decreases and that a collaborative approach to sustaining volunteering is needed.